Anticipated next‐day demand affects the magnitude of the cortisol awakening response, but not subjective or objective sleep. (1st June 2017) - Elder, Greg J.; Barclay, Nicola L.; Wetherell, Mark A.; Ellis, Jason G.
Summary: Whilst the association between sleep and stress is well established, few studies have examined the effects of an anticipated stressor upon sleep and relevant physiological markers. The aim of the present study was to examine whether an anticipated stressor in the form of next‐day demand affects subjective and objective sleep, and multiple indices of the cortisol awakening response. Subjective and objective sleep and the cortisol awakening response were measured over three consecutive nights in 40 healthy adults in a sleep laboratory. During their second night, participants were informed that they would either be required to complete a series of demanding cognitive tasks, in a competition format, during the next day (anticipation condition; n = 22), or were given no instruction (sedentary condition; n = 18). Sleep was measured subjectively using sleep diaries, objectively using polysomnography, and saliva was measured at awakening, +15, +30, +45 and +60 min each morning, from which cortisol awakening response measurement indices were derived: awakening cortisol levels, the mean increase in cortisol levels and total cortisol secretion. There were no between‐group differences in subjective or objective sleep in the night preceding the anticipated demand; however, compared with the sedentary condition, those in the anticipation group displayed a larger mean increase in cortisol levels, representing the cortisol awakening response magnitude, on the morning of the anticipated demand. Overall, the results suggest that whilst anticipated stress affected the subsequent cortisol awakening response, subjective and objective sleep remained undisturbed. It is possible that the timing of an anticipated stressor, rather than its expected duration, may influence subsequent sleep disruption.